Ideas in Circulation: Attilio Corrêa Lima, Armando Augsuto de Godoy and The Urbanistic Conceptions of Goiânia - Guimarães, Leonardo Dimitry Silva (Risco - Journal of Architecture and Urbanism, 2021)
Goiânia, product of a political scenario post-Coup of 30, is idealized through the discourse of progress. As outcome of this logic, however, the city should express a feature aligned to the new time enunciated. For its conception, expressive names are invited, such as Attilio Corrêa Lima e Armando Augusto de Godoy. These actors, however, print their visions in a non-tight way, but rather from selective loans, translations and transformations. Under this guideline, the paper proposes to understand the genesis of the decisions that conditioned the morphology of the capital, through the perspective of formation and action of its planners.